2005
DOI: 10.1042/bj20041736
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the prolyl hydroxylase domain protein 2 (phd2/egln-1) gene: identification of a functional hypoxia-responsive element

Abstract: The HIFs (hypoxia-inducible factors) are a family of heterodimeric transcription factors essential for the adaptation of cells to reduced oxygen supply. Three human PHDs (prolyl hydroxylase domain proteins, PHD1-PHD3) initiate oxygen-dependent degradation of HIF-alpha-subunits in normoxia. RNA interference directed against PHD2, but not PHD1 or PHD3, is sufficient to stabilize HIF-1alpha in normoxia. Therefore PHD2 is regarded as the main cellular oxygen sensor. PHD2 itself is up-regulated by hypoxia and may t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
130
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(142 citation statements)
references
References 45 publications
9
130
0
3
Order By: Relevance
“…We and others have previously reported that hypoxic regulation of PHD3 is dependent on HIF activity (5,18,(21)(22)(23). To ascertain whether PHD3 regulation by cytokines involved the HIF signaling pathway, loss-of-function studies were performed.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported that hypoxic regulation of PHD3 is dependent on HIF activity (5,18,(21)(22)(23). To ascertain whether PHD3 regulation by cytokines involved the HIF signaling pathway, loss-of-function studies were performed.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus CRE site (5 0 -TGACGTC-3 0 ) in pAREG(À120/ þ 120), located 65 nucleotides upstream of the transcriptional start site, was mutated to (5 0 -TGAaaTC-3 0 ) by site-directed mutagenesis. The PHD2 luciferase reporter plasmid pP2P(À603/ þ 3)wt is a truncated version of the previously published human PHD2 promoter (Metzen et al, 2005). Cells were cotransfected with 200 ng reporter plasmid and 10 ng pRLSV40 Renilla luciferase reporter vector (Promega, Du¨bendorf, Switzerland) and luciferase reporter gene activity was determined using the dual-luciferase reporter assay system according to the manufacturer's instructions (Promega).…”
Section: Reporter Gene Assaysmentioning
confidence: 99%
“…7, D and E) under normoxic conditions. The successful knockdown of HIF-1␣ after transfection of HIF-1␣ siRNA was verified by HIF-1␣ immunoblots as well as by diminished expression of PHD2, which is hypoxia-inducible by HIF-1 itself (36).…”
Section: Rhoa/rock Activity Is Responsible For Cof-1 Phosphorylation mentioning
confidence: 99%